Implementasi Meaning Theory dan Drill Theory pada Pembelajaran Statistika - Rintis Rizkia Pangestika; Titi Anjarini (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2019)
The purpose of this study was to determine the effectiveness of the application of Meaning Theory and Drill Theory in statistical learning. The population in this study were the fourth semester PGSD students, amounting to 150 students and the sample in this study was 105. This type of research is a quasi-experimental quantitative research method. Data collection through tests through question instruments. The data analysis technique uses the t-test through a prerequisite test for data normality and homogeneity. From the results of the prerequisite test analysis of the post-test data of the experimental group and the control group, it can be concluded that the two groups are normally distributed and homogeneous. Based on the testing criteria, if the data are normally distributed and homogeneous, then proceed with the T test. From the results of the calculation, the results of the hypothesis test are tcount> t table (5.229> 1.990) with a significance of <0.05, 0.00. Then it can be said that H0 is rejected or Ha is accepted. Thus, it can be concluded that statistical learning outcomes through the application of meaning theory and drill theory are more effective than lecture or conventional methods.